From Self-Reflection to Action: Supporting Teachers as Agentic Professionals to Improve Digital Competence Capacity - Kyza A., Eleni; Georgiou, Yiannis (My University, 2025)
In today's rapidly evolving digital landscape, teachers’ digital competence is a critical component of professional development. This study investigated how self-determination processes, such as self-reflection and self-efficacy, can empower teachers to enhance their digital skills. Self-determination theory suggests that individuals can achieve their personal goals if they have autonomy (feeling of control), competence (feeling capable) and are connected to others (feeling of community). When these psychological needs are fulfilled, individuals gain agency to take control of their own learning. Data were collected from three case studies with in-service teachers. Qualitative analyses showed that teachers required substantial scaffolding to progress from awareness to self-regulation and agency. Findings indicate the importance of fostering an environment where teachers can critically assess their digital competence and set meaningful goals for improvement. We conclude our discussion with recommendations for designing professional development programs that encourage selfregulated learning and reflective practices to promote digital competence.